2015
DOI: 10.1186/s13567-015-0275-z
|View full text |Cite
|
Sign up to set email alerts
|

Live attenuated African swine fever viruses as ideal tools to dissect the mechanisms involved in viral pathogenesis and immune protection

Abstract: African swine fever virus (ASFV) is the causal agent of African swine fever, a hemorrhagic and often lethal porcine disease causing enormous economical losses in affected countries. Endemic for decades in most of the sub-Saharan countries and Sardinia, the risk of ASFV-endemicity in Europe has increased since its last introduction into Europe in 2007. Live attenuated viruses have been demonstrated to induce very efficient protective immune responses, albeit most of the time protection was circumscribed to homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 43 publications
8
105
1
1
Order By: Relevance
“…Regarding the role played by cytokines in the mechanisms of protection, conversely to what other studies suggested (Lacasta et al., 2015), IL-10 did not seem to contribute to controlling ASFV replication or avoiding harmful inflammation. Instead, and given the ability of IL-10 to impair or counteract the innate and adaptive immune response (Moore et al., 1993, Moore et al., 2001), the high concentrations detected after challenge in most of the immunised non-protected pigs might be linked to a failure of protective immune responses that might compromise the pigs' survival.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Regarding the role played by cytokines in the mechanisms of protection, conversely to what other studies suggested (Lacasta et al., 2015), IL-10 did not seem to contribute to controlling ASFV replication or avoiding harmful inflammation. Instead, and given the ability of IL-10 to impair or counteract the innate and adaptive immune response (Moore et al., 1993, Moore et al., 2001), the high concentrations detected after challenge in most of the immunised non-protected pigs might be linked to a failure of protective immune responses that might compromise the pigs' survival.…”
Section: Discussionsupporting
confidence: 56%
“…Other studies where pigs were immunised with OURT88/3 (Oura et al., 2005) suggested that although anti-ASFV antibodies were not enough to protect pigs, their role should not be completely ruled out. As for cellular immune responses, subsets of NK cells and CD8 + T-cells have been indicated to be relevant for protection induced by some live attenuated vaccine candidates (Scholl et al., 1989, Leitão et al., 2001, Oura et al., 2005, Lacasta et al., 2015) and DNA vaccines (Argilaguet et al., 2012, Lacasta et al., 2014). More specifically, in protected pigs immunised by oronasal route with ASFV NH/P68 isolate, cytotoxic activity was mediated by CD8 + cells which lysed macrophages infected with homologous isolates under restriction of class I swine leukocyte antigen (SLA) (Martins et al., 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those animals inoculated with E75 showed low Ct values at 7 dpi coinciding with the peak of virus replication and ASF clinical signs, while in contrast, inoculation of the same dose of the homologous attenuated E75CV1 strain showed no amplification. The animals infected with E75CV1 and re-inoculated with the BA71 virulent strain showed amplification levels similar to those found after E75 infection, correlating with the lack of cross-protection observed for these two strains [15]. As expected, the negative control animal did not show any specific PCR amplification (Table 2).…”
Section: Resultssupporting
confidence: 66%
“…Experimental vaccines based on the use of an inactivated virus or virus subunits have failed to induce solid protective immunity [3,4,5,6]. Homologous protective immunity does develop in swine surviving infections with moderately virulent or attenuated ASFV isolates [7,8,9,10]. Swine immunized with live attenuated ASFVs containing genetically engineered deletions of specific virulence-associated genes are similarly protected when challenged with homologous parental viruses.…”
Section: Introductionmentioning
confidence: 99%